The white ambition marketing strategies and market volume of skin-whitening products in Iloilo City - Culaba, Thea Faye C.; Daguman, Ellaine Rae O.; Dahab, Lara Faith T.; Ellorquez, Lyka Rev C. (2016.)
This study covers the relationship of the marketing strategies employed by the companies of skin-whitening products, and the actual market volume of these products in Iloilo City for the years 2013-2015, the level of awareness of the Ilonggo consumers, the effectiveness of the platforms used, the purchase frequency, the personal motivations of the buyers and the recommendations to be given to the brand companies, and retail outlets to further increase sales. A total of 50 active consumers in the city of Iloilo were selected to become respondents to the survey given. Four retail companies were selected, namely Gaisano Guanco, Supermart Jaro, SM Delgado Supermart, and Iloilo Society Commercial. These outlets were given an interview schedule. The effectiveness of the strategies employed and the level of awareness was the key influencer of the fluctuations, or the increase in the market volume and the buying frequencies of the consumers, and these were the main points of analysis in this study. Mixed method in sequential explanatory technique was used in the examination of data. The significance of this study is not only limited to the researchers, rather it has an importance to a wider scope of people, such as the companies, and the consumers ; wherein additional knowledge may be added to the different studies that concern the two. Alongside this, to provide people with the recent status of the fastest-growing industry in the country, and also to serve as a guide to those who would want to enter into this business. The Philippines is one of the most active consumers of skin-lightening products in Asia. According to a survey done by Synovate, one out of two Filipinas are known to be users. In the search for the relationship between the marketing strategies and the market volume, the findings indicate that there is a direct correspondence between them. The level of awareness is the moderating variable to which the researchers derived the answer. As the efficiency of the marketing strategies employed by companies rise, there has been a notable increase in the number of units sold in retail outlets for the past three years. In Iloilo City, the level of awareness is moderate throughout each consumer, wherein TV and Radio advertisements remain the frontrunner in propagating the information to the public. The marketing mix also plays an integral role in the purchasing decisions the consumer makes, such as the price, promotion place, and product information. Most of the respondents are moderately knowledgeable about these products, also a large number of them answered that they were frequent users, and that with the increase in marketing strategies, these buyers would either increase their buying frequencies, or maintain their usual purchases.
[Research Paper] ( Mgt 199-Management Research). -- Iloilo City : University of the Philippines in the Visayas - College of Management, December 2, 2016.